PENGARUH VARIABEL RUANG FISKAL, DAU DAN DBH TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PEMERINTAH PROVINSI - Slamet Widodo (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2018)
The purpose of this research is to analyze the impact of fiscal space, General Allocation Fund (DAU) and Revenue Sharing Fund (DBH) to Human Development Index (HDI/IPM) in provincial level. The reseach used data of IPM, fiscal space, DAU, and DBH for the period of 2006-2015 from Central Agency of Statictic (BPS), Ministry of Finance, and other related institutions. Reseach methology used Regression of Data Panel with Fixed Effect Model and Ordinary Least Square estimation. The results of the reseach show that the fiscal space, DAU and DBH variables significantly influence the HDI of provincial government with negative direction.